Avaliação de uma política pública a partir das dimensões sociais: estudo de caso da Escola Areninha Pirambu - Oliveira, Mário Barbosa (2025)
The dissertation aims to evaluate the Escola Areninha project in the Pirambu neighborhood of Fortaleza, Ceará. Through prolonged field immersion, the research sought to analyze how this initiative, which combines sports, education, and culture, influences the lives of young people, their future perspectives, and their relationship with the community. The study seeks to understand how Escola Areninha contributes to identity formation, citizenship development, and social inclusion. Using ethnography as a methodology, participant observations were conducted in different spaces of Escola Areninha. The collected data were analyzed in light of theoretical frameworks addressing the relationship between public policies, education, culture, and social development. The evaluative research revealed that Escola Areninha plays a fundamental role in the lives of young people in Pirambu, providing a safe and welcoming space for the development of their potential. The sports, cultural, and educational activities promoted by the school contribute to the construction of social bonds, the development of socio-emotional skills, and the expansion of opportunities. Furthermore, the research highlighted the importance of Escola Areninha as a space of resistance that can help overcome challenges in the pursuit of new narratives about youth and the community.